2013
DOI: 10.2136/vzj2013.01.0006
|View full text |Cite
|
Sign up to set email alerts
|

Shrub Hydropedology: Preferential Water Availability to Deep Soil Layer

Abstract: The complex interactions between shrub traits, soil structure, and soil water dynamics are not well understood yet. This study investigated rainfall partition by C. microphylla L., spatial soil water pattern, soil hydraulic conductivity, and soil macropores to ascertain preferential water flow to deep soil layer by shrub. Results indicated that high variability in throughfall existed within individual shrub stand: average coefficient of variation was 0.36 ± 0.13 for shrub and 0.15 ± 0.13 for interspace grass. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 69 publications
(104 reference statements)
6
26
0
Order By: Relevance
“…Note: BA is the branch inclined angle; P is the precipitation amount; CK and SP are the abbreviations of C. korshinskii and S. psammophila, respectively. available moisture in dryland ecosystems (Dunkerley, 2000;Yang, 2010;Návar, 2011;Li et al, 2013). That agreed with the findings of Dong and Zhang (2001) that S. psammophila belonged to the water-spending paradigm from the aspect of leaf water relations and anatomic features, and the finding of Ai et al (2015) that C. korshinskii belonged to the watersaving paradigm and had larger drought tolerance ability than S. psammophila from the aspect of root anatomical structure and hydraulic traits.…”
Section: Effects Of Precipitation Threshold To Produce Stemflowsupporting
confidence: 80%
See 1 more Smart Citation
“…Note: BA is the branch inclined angle; P is the precipitation amount; CK and SP are the abbreviations of C. korshinskii and S. psammophila, respectively. available moisture in dryland ecosystems (Dunkerley, 2000;Yang, 2010;Návar, 2011;Li et al, 2013). That agreed with the findings of Dong and Zhang (2001) that S. psammophila belonged to the water-spending paradigm from the aspect of leaf water relations and anatomic features, and the finding of Ai et al (2015) that C. korshinskii belonged to the watersaving paradigm and had larger drought tolerance ability than S. psammophila from the aspect of root anatomical structure and hydraulic traits.…”
Section: Effects Of Precipitation Threshold To Produce Stemflowsupporting
confidence: 80%
“…Dryland shrubs generally experienced several wetting-drying cycles (Cui and Caldwell, 1997) when rains were sporadic. As an important source of rhizosphere soil moisture at dryland ecosystems (Dunkerley, 2000;Yang, 2010;Návar, 2011;Li et al, 2013), a considerable amount of stemflow could be produced by various species and infiltrated into deep soil during heavier rains. However, during lighter rains, the larger amount stemflow produced in more efficient manner might benefit xerophytic shrubs, as more soil moisture could be recharged especially at the root zone.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of the hydrologic balance induced by desert vegetation is crucial for assessing the spatial patterns, establishment and permanence of vegetation in vast desert areas (Reynolds et al, 1999;Rietkerk et al, 2004). Shrubs are the dominant vegetation and play an important role in the desert ecosystems by altering the hydrological, physical and biological soil environment induced by their canopies (Li et al, 2013;McKell, 1975). Therein, from a hydrologic point of view, individual shrub canopies exert a significant control by modifying both evaporation and redistribution of incident rainfall (Domingo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that resource islands, compared to interspaces, modify soil water properties that can lead to changes that serve as a positive biophysical feedback to plant establishment and growth (Bhark and Small, 2003;Kizito et al, 2012;Rango et al, 2006). Plant-soilhydrological processes in resource islands are complex, varying greatly across spatiotemporal scales, by depth, and an area of incipient research (Aguilera et al, 1999;Jury et al, 2011;Li et al, 2013;Schade and Hobbie, 2005). In our study, soils of native shrubs had significantly greater soil water content (SWC) than bare soil at 10 cm depth, however, no significant difference in SWC was found among soils from interspaces, mango alone, and intercropped mango + shrub.…”
Section: Mango + Shrub Soil Moisture and Phmentioning
confidence: 99%